Multiple magnetic foreign bodies causing complex intestinal fistula - Gayatri S. Munghate; A.S. Reddy; Minnie Bodhanwala (Elsevier, 2020)
Foreign body ingestion is a common occurrence in young children. Majority are associated with low morbidity [1]. The magnetic foreign body ingestion related injuries have increased in last decade. These are associated with significant morbidity [2]. We describe a case of one such multiple small magnets ingestion resulting in formation of complex fistula between stomach and two loops of small intestine. Child had to undergo laparotomy.